P117 A qualitative assessment of UK sexual healthcare professionals' views on targeted vaccination against human papillomavirus (HPV) for men who have sex with men (MSM). (18th May 2015) - Nadarzynski, Tom; Llewellyn, Carrie; Richardson, Daniel; Pollard, Alex; Smith, Helen
Abstract : Background: Female-only HPV vaccination will fail to protect MSM against HPV and its sequelae i.e. genital warts and anal cancers. In the absence of gender-neutral HPV vaccination, targeted vaccination for MSM at sexual health clinics offers a valuable preventive opportunity. Aims: To identify sexual healthcare professionals' (SHCPs) perceived barriers and facilitators for MSM-targeted HPV vaccination. Methods: Nineteen telephone interviews, with UK-based self-referred SHCPs (13 doctors, 3 nurses, 3 health advisers), were conducted in October and November 2014. The interviews were recorded and transcribed verbatim. Data were analysed thematically by two researchers. Results: Nine themes were identified. The major perceived barriers were: 'concerns about vaccination programme equity and equality'; 'concerns about vaccination effectiveness'; 'challenges with targeting MSM'; 'obstacles with HPV vaccination delivery' and 'negative public reaction to targeting MSM'. The main facilitators were: 'policies and guidelines'; 'rising awareness'; 'acceptable settings' and 'adequate vaccination procedures'. While SHCPs expressed varied and sometimes contradictory views on MSM-targeted HPV vaccination, most agreed that HPV vaccination, inclusive of all school-aged boys, would be the most suitable strategy. Conclusion: Although SHCPs recognised a need to protect MSM against HPV, several challenges and obstacles associated with the introduction of MSM-targeted HPV vaccination in the UK were reported. Solutions on individual, organisational and public levels were offered. SHCPs' perspectives and concerns need to be addressed when developing policies and guidelines for a potential MSM-targeted HPV vaccination. Future research needs to examine whether negative views of SHCPs towards MSM-targeted HPV vaccination are associated with lower HPV vaccine acceptability and uptake in MSM.